Sistem Informasi Monitoring Orang Tua Terhadap Kehadiran Anak di Sekolah Berbasis Website - Ade Hendini; Dwi Kurniawati (FKOM UNIKU, 2024)
Student attendance at school is very important to ensure that they get a good education and are successful in the future. Parents are an important part in supporting their children's education, communication between parents and schools is very important in supporting children's education. Currently, there are still many schools that use attendance books as a medium for recording student attendance. This makes it difficult for parents to monitor their child's attendance regularly, especially if they are at work or unable to visit school every day. The purpose of writing this Final Project (TA) is to create a website-based application to monitor student attendance at SMP Negeri 13 Sungai Raya, which is in Kabupaten Kubu Raya. The method used in developing this software uses the waterfall method and data collection methods. With this web-based application, it can assist parents in monitoring their children's attendance at school and increase parental involvement in children's education by providing accurate and up-to-date information about children's attendance at school